Non-vitamin K antagonist oral anticoagulants for heparin-induced thrombocytopenia. A systematic review of 54 reported cases - Shatzel, Joseph J.; Crapster-Pregont, Meg; Deloughery, Thomas G. (Thrombosis and Haemostasis, 2016)
Supplementary Material to this article is available at www.thrombosis-online.com.